An analysis of standardized data for fog computing storage capacity using non-relational database - Naim @ Mohayat, Mohd Hariz; Salahuddin, Lizawati; Abdul Hamid, Mohd Hakim; Basiron, Halizah; Lee, Mei Ph’ng; Mohamad Zain, Jasni; Kamarularifin, Abd Jalil (World Academy Of Research In Science And Engineering (WARSE), 2020)
Computer applications nowadays relies on physical storage either to store the computation information or for the application itself. As the application become more complex and being used day after day, the data will be growing causing issue with lack of free space especially in fog computing where the storage resource is limited. Despite increasing disk storage or even migrating the data into the cloud would resolve this issue but this would also increase the overall cost as well. Thus, the objective of this paper is to analyse the difference between non-relational database with relational database in term of storage capacity. First the data from relational database will be taken and converted into a standard format and later turned into non-relational database. The result from the analysis will provide motivation for proposing database storage to be implemented in fog computing environment